Longitudinal Associations Between Brain Volume and Knee Extension Peak Torque - Osawa, Yusuke (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Muscle strength and brain volume decline with aging; changes in the brain manifested as change in volume may play a role in age-related strength loss, but this hypothesis has never been tested longitudinally. We examined longitudinal associations between brain volume changes and knee extension peak torque change in participants of the Baltimore Longitudinal Study of Aging. METHODS: Brain volumes and isokinetic concentric knee extension peak torque at 30 deg/s were measured in 678 participants (55.2% women; baseline age, 50.1–97.2 years; median follow-up time in those who visited two or more times (n = 375, 4.0 [interquartile range IQR, 2.3–5.0] years). Correlations between longitudinal changes in brain volumes and knee extension peak torque were examined using bivariate linear mixed-effects models, adjusted for baseline age, sex, race, education, and intracranial volume. RESULTS: Greater decline in muscle strength was associated with greater atrophies in global gray matter, temporal lobe, frontal gray matter, temporal gray matter, superior frontal gyrus, inferior frontal gyrus, supramarginal gyrus, middle temporal gyrus, inferior temporal gyrus, and occipital pole (r ranging from .30 to .77, p < .05). After multiple comparison adjustment, only larger decrease in middle temporal gyrus remained significantly related to larger decrease in muscle strength (q = 0.045). CONCLUSIONS: In older adults, declines in knee extension muscle strength co-occurred with atrophies in frontal, temporal, and occipital gray matter. These findings support the idea that age-related knee extension muscle strength is linked with atrophy in some specific brain regions related to motor control.